Islamic Religious Education Learning Management Through The Use Of Chatbots To Increase Student Interactivity And Motivation - Akbar, Fadhil (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2025)
The development of artificial intelligence (AI) opens up new opportunities in the management of more interactive and adaptive learning, including in Islamic Religious Education (PAI). However, many PAI learning practices are still conventional, teacher-centered, and have minimal interaction, resulting in low student motivation to learn. This study aims to examine PAI learning management through the use of chatbots to increase student interactivity and motivation, with a focus on planning, implementation, and evaluation of learning. This research uses a qualitative approach with a descriptive-analytical design. Data was collected through observations, semi-structured interviews, and documentation of PAI teachers, students, and schools involved in the implementation of chatbot-based learning. Data analysis is carried out through the stages of reduction, data presentation, and conclusion drawing by triangulating sources and techniques to maintain the validity of the data. The results of the study show that the systematic use of chatbots can increase student interactivity and motivation. In the planning stage, the chatbot is integrated with PAI materials that are conceptual and reflective. In implementation, chatbots create a dialogical, responsive, and student-centered learning environment, which encourages active participation and independent learning. In evaluation, chatbots assist teachers in process-based formative assessments. This study concludes that chatbots can be a strategic instrument in PAI learning management if positioned as an integrated pedagogical support, not a substitute for the role of educators.